2016
DOI: 10.1002/anie.201602996
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Chromium(III) to Transferrin Could Be Involved in Detoxification of Dietary Chromium(III) Rather than Transport of an Essential Trace Element

Abstract: Cr(III) binding to transferrin (Tf; the main Fe(III) transport protein) has been postulated to mediate cellular uptake of Cr(III) to facilitate a purported essential role for this element. Experiments using HepG2 (human hepatoma) cells, which were chosen because of high levels of the transferrin receptor, showed that Cr(III) binding to vacant Fe(III) -binding sites of human Tf effectively blocks cellular Cr(III) uptake. Through bio-layer interferometry studies of the Tf cycle, it was found that both exclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(103 citation statements)
references
References 48 publications
12
87
0
Order By: Relevance
“…The high amount of Fe in the diet might inhibit Cr absorption in the small intestine. Under normal conditions, only about 30% of the potential Fe(III) binding sites in Tf are occupied, leaving the unoccupied binding sites to potentially bind other metal ions [ 8 , 9 , 40 , 41 ]. When the saturation of transferrin with iron rises to over 50%, iron competes with chromium binding, affecting its transport [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high amount of Fe in the diet might inhibit Cr absorption in the small intestine. Under normal conditions, only about 30% of the potential Fe(III) binding sites in Tf are occupied, leaving the unoccupied binding sites to potentially bind other metal ions [ 8 , 9 , 40 , 41 ]. When the saturation of transferrin with iron rises to over 50%, iron competes with chromium binding, affecting its transport [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…[18,23] It remains to be established whetherV III -Tf is taken into cells by the same receptormediated endocytosis mechanism as Fe III -Tf (C,S cheme 1), since recent studies showed that aC r III -Tf analog is excluded from cells due to disrupted interactions with the Tf receptor on the cell surface. [28] V V speciesc ause intracellular inhibition of protein tyrosine phosphatases( PTPs), either through reversi-ble binding to Cys residues in the enzymea ctive centers or via strongly oxidizing peroxido vanadates (formedinsitu) that irreversibly oxidize Cys residues to sulfinic acid (Scheme 1). [4,29,30] Both events lead to increased phosphorylation of regulatory proteins to enhance cell signaling, including insulin signaling.…”
Section: Vanadium Complexes As Pro-drugsmentioning
confidence: 99%
“…Cellular Ru uptake was measured following our published method . Cell treatments were performed in triplicate in six‐well plates, either by growing MDA‐MB‐231 or A549 cells to ≈80 % confluence and then incubating them with 50 μ m Ru for 4 h (Figure A), or seeding 1.0×10 5 viable cells per well and growing them to near‐confluence for 72 h in the presence of 20 μ m Ru (Figure B).…”
Section: Methodsmentioning
confidence: 99%